Penerapan Teknik Bordir Kombinasi Quilting Motif Daun Ketela Pada Blus Batik pecelan Khas Madiun - Vio Aulia Nurhalisa Mahmud; Yuhri Inang Prihatina (Universitas Negeri Surabaya, 2023)
Cassava leaves have a distinctive feature in batik pecelan typical of Madiun, batik pecel / pecelan is one of the typical foods of the Madiun region and is an icon of the city of Madiun. In pecelan food there are vegetables accompanying pecel sauce such as cassava leaves, sprouts, long beans, turi flowers, kale and so on. The purpose of the research is to describe the process of developing embroidery techniques combined with Quilting applied to batik pecelan outers as one of the new innovative developments in batik pecelan typical of Madiun. This method consists of 4 research stages: discover, define, develop and deliver. In the initial stage, determining the source of the idea, namely the cassava leaf motif taken from one of the motifs in pecelan batik which will be applied to the quiting technique and then given a completion using the embroidery technique. In the second stage, researchers made a moodboard and developed 5 designs, one selected design was realized into a blouse. The third stage is by applying the embroidery technique combined with quilting on the cassava leaf motif. The fourth stage is the finished blouse according to the embroidery technique combined with the quilting technique as a decoration.